Problem Gambling: Summarizing Research Findings and Defining New Horizons - Tobias Hayer (Frontiers Research Topics, 2018)
In 2003, Rachel A. Volberg wrote: "Why is it that gambling is not even on the radar when we consider the array of risks that adolescents must confront as they move towards adulthood?" Nowadays, after thirteen years, although much more is known about this particular form of risk behavior, there is still a general tendency, at least among laypersons, to not perceive gambling as a potential danger for youth and other population segments (e.g., individuals with migration background, seniors, sports professionals). However, the latest edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5, American Psychological Association, 2013) included Gambling Disorder as the only condition in the Section Non-Substance-Related Disorders. Moreover, it is specified that the disorder can indeed occur in adolescence or young adulthood. Despite this fact, theoretical and applied research on problem gambling with regard to adolescence and other risk groups is still in its infancy. For this reason, it seems to be important to organize a Research Topic on gambling in Frontiers in Psychology in order to i) highlight the necessity of considering gambling as a potential harmful activity; ii) summarize the state-of-art of international research on different aspects of the topic; and iii) offer important novel findings relevant for advancing knowledge in the field of gambling. Different types of research articles will be provided including original articles, systematic/scoping reviews, meta-analyses, case reports, and commentaries. These contributions will be focused on the following most important areas in gambling research: Measurement (Which are the most widely used instruments to assess gambling-related problems as well as proximate constructs and what are their psychometric properties? Are there new instruments to detect adolescent problem gamblers?), Protective and risk factors (What do we know about ecological and individual influences on gambling behavior? Which factors affect problem gambling most and in which way?), Prevention (Which are the most promising prevention programs implemented until now? Which are necessary ingredients for effective prevention?), Treatment (When individuals seek help for their gambling-related problems, which are the clinical treatments that are offered? Do we have evidence for treatment effectiveness for different subgroups?). To try to fulfill this goal in the most comprehensive way, researchers from different countries and with specific competencies and interests will be contacted and encouraged to submit a contribution. Through the integration of international and multidisciplinary contributions, i) new challenges in the field of gambling will be identified (e.g., definition of specific at-risk groups, specification of effective interventions in terms of best practices) and ii) new research routes (e.g., the use of behavioral data) will be outlined in order to build a comprehensive understanding of problem gambling. The overall aim is to summarize the state of art, to propose original novel findings, and to outline new directions in gambling research.